The Importance Of Music Science To Students With Speech Impairments In The Context Of Inclusive Education - Mastura Abduvakhobovna Asadullayeva (Euro Asian Journal Publishing, 2024)
the relevance of musical activities for children with disabilities is that they allow each child, regardless of his abilities and abilities, to reveal and prove themselves, learn to understand and love songs, music, participate in Concert Activities, overcome some deviations in physical and mental development. In this regard, it is possible to highlight the positive role of musical training in improving the physical and spiritual-psychological state of children with disabilities, correcting existing shortcomings in the emotional-voluntary sphere, developing aesthetic perception, etc
Keywords: students with disabilities; pedagogy; music; quality of Education